A ceramic brake pad for new energy vehicles and a preparation method thereof
Patent Information
- Application Number
- CN202410409144.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-04-07
AI Technical Summary
Existing brake pads for new energy vehicles cause heavy metal powder pollution, noise, vibration, and thermal expansion and cracking during friction braking, affecting environmental protection and driving comfort.
Ceramic brake pads, composed of composite wear-resistant and noise-reducing materials, composite heat-resistant and high-temperature-resistant materials, and composite friction materials, are prepared through thermoforming, thermosetting, and ablation to form a porous and dense structure, thereby reducing noise and vibration and improving thermal stability.
It achieves zero heavy metal pollution, reduces noise, improves the strength and lifespan of friction materials, and solves the environmental protection and heat resistance problems of brake pads for new energy vehicles.
Smart Images

Figure CN118290067B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of vehicle braking system technology, specifically relating to a ceramic brake pad for new energy vehicles and its preparation method. Background Technology
[0002] In recent years, with the development of technology and people's emphasis on low-carbon and environmentally friendly travel, the new energy vehicle market has been booming. In 2023, the production and sales of new energy vehicles both approached the 10 million mark, and the market share reached 31.6%. New energy vehicles have received unanimous praise for their low carbon and environmental protection, high transmission efficiency, driving comfort, and policy support. However, there are still some shortcomings in the existing technology that limit the development of new energy vehicles.
[0003] The following issues have caused significant concern in the braking system field: 1. Brake materials contain a large amount of metal, which, during friction braking, releases metal powder into the air, causing heavy metal pollution, contradicting the low-carbon and environmentally friendly concept of new energy vehicles; 2. Due to material limitations, braking systems still generate considerable noise during friction braking. Since vehicle noise primarily originates from the engine and braking system, and the noise and vibration levels of electric motors in new energy vehicles are currently far lower than those of traditional internal combustion engines, the noise generated by the braking system is currently the main noise source for new energy vehicles, severely reducing driving comfort; 3. Frequent braking leads to thermal expansion and cracking problems due to the limitations of ordinary brake pad formulations, resulting in a short lifespan for brake pads. Because new energy vehicles have higher torque and faster acceleration, braking is more frequent than in traditional fuel vehicles. This causes brake pads to continuously generate high temperatures. Under continuous high temperatures, ordinary brake pads experience thermal expansion and cracking, leading to material deformation and softening, and in severe cases, material detachment due to high temperatures. These problems hinder the development of new energy vehicle technology. Therefore, it is necessary to study a ceramic brake pad for new energy vehicles to solve the technical problems of heavy metal powder pollution, high noise, high vibration, and temperature difference resistance caused by the friction between the existing ordinary brake pads and brake discs in new energy vehicles. Summary of the Invention
[0004] To address the aforementioned shortcomings in existing technologies, this invention provides a ceramic brake pad for new energy vehicles and its preparation method, thereby solving technical problems such as heavy metal powder pollution, high noise, high vibration, and poor temperature resistance when ordinary brake pads for new energy vehicles rub against the brake disc.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A ceramic brake pad for new energy vehicles is made from raw materials that are a mixture of composite wear-resistant and noise-reducing materials, composite heat-resistant and high-temperature resistant materials, and composite friction material adjustment materials, through thermoforming, thermosetting, and ablation. The composite wear-resistant and noise-reducing materials account for 25-59% of the total material composition, the composite heat-resistant and high-temperature resistant materials account for 26-58% of the total material composition, and the composite friction material adjustment materials account for 18-38% of the total material composition.
[0006] Furthermore, the composite wear-resistant and noise-reducing material group contains 5-9% by weight of potassium magnesium titanate flakes, 3-8% by weight of silicon carbide, 3-10% by weight of tin sulfide, 4-10% by weight of CIRCOLIT-T powder, 5-12% by weight of fiber filler, and 5-10% by weight of composite silicate whiskers.
[0007] Furthermore, the composite heat-resistant and high-temperature resistant material group contains 2-6% by mass of aramid fiber, 4-8% by mass of silicon boron nitrogen carbon fiber, 5-10% by mass of hafnium carbide, 5-9% by mass of zirconium dioxide nanofiber, 5-13% by mass of polycrystalline mullite fiber, and 5-12% by mass of high-alumina aluminum silicate.
[0008] Furthermore, the composite friction material adjustment group contains 5-10% by weight of special phenolic resin, 6-12% by weight of cashew shell oil friction powder, 3-8% by weight of quartz fiber, and 4-8% by weight of silicon nitride fiber.
[0009] This invention provides a method for preparing ceramic brake pads for new energy vehicles as described in the above technical solution, comprising the following steps: S1. Prepare raw materials: Potassium magnesium titanate flakes, silicon carbide, tin sulfide, CIRCOLIT-T powder, fiber filler, and composite silicate whiskers are placed in an automatic mixer in proportion to form a composite wear-resistant and noise-reducing material group. Aramid fiber, silicon boron nitrogen carbon fiber, hafnium carbide, zirconium dioxide nanofiber, polycrystalline mullite fiber, and high-alumina aluminum silicate are placed in an automatic mixer in proportion to form a composite heat-resistant and high-temperature resistant material group. Special phenolic resin, cashew shell oil friction powder, quartz fiber, and silicon nitride fiber are placed in an automatic mixer in proportion to form a composite friction material adjustment group. The prepared composite wear-resistant and noise-reducing material group, composite heat-resistant and high-temperature resistant material group, and composite friction material adjustment group are placed in an automatic mixer for orderly integration to obtain the raw materials. S2. Thermoforming: The raw material prepared in step S1 is placed in a semi-automatic single-cylinder single-cavity multi-station equal density rotary press for semi-finished product forming and pressing. The hot pressing pressure in this step is 25-35 MPa, the hot pressing temperature is 180-220℃, and the hot pressing time is 300-420 s. S3. Heat curing: Place the brake pad semi-finished product prepared in step S2 in an oven for heat curing. Step 1: Slowly raise the temperature from room temperature to 150~200℃ and cure for 1 hour. Step 2: Rapidly raise the temperature from 150~200℃ to 200~260℃ and cure for 1.5 hours. After curing, allow the temperature to drop naturally. Open the oven door when the temperature drops below 80℃. Remove the brake pad semi-finished product after the temperature drops to room temperature. S4. Final processing: Place the brake pad semi-finished product prepared in step S3 into an automatic grinding equipment to complete the processing of flat grinding, grooving, chamfering, and oblique grooves and J-shaped angles of the brake pad. S5. Ablation process: The brake pads that have completed the final processing in step S4 are placed in a brake pad ablation machine to automatically complete the ablation process. After the ablation machine is rapidly heated from room temperature to 550°C, the friction surface of the brake pads is attached to the ablation machine and ablated for 5 minutes before the brake pads are removed.
[0010] Furthermore, in step S1, when preparing the composite wear-resistant and noise-reducing material group, the automatic mixer blade speed is 2000~2600 r / min, the auxiliary blade speed is 500~750 r / min, and the mixing time is 6~10 min.
[0011] Furthermore, in step S1, when preparing the composite heat-resistant and high-temperature resistant material group, the automatic mixer blade speed is 1800~2300 r / min, the auxiliary blade speed is 450~700 r / min, and the mixing time is 6~10 min.
[0012] Furthermore, in step S1, when preparing the composite friction material adjustment group, the automatic mixer blade speed is 2200~2800 r / min, the auxiliary blade speed is 700~850 r / min, and the mixing time is 5~8 min.
[0013] Furthermore, in step S1, when mixing the composite wear-resistant and noise-reducing material group, the composite heat-resistant and high-temperature resistant material group, and the composite friction material adjustment group, the automatic mixer blade speed is 1500~1700 r / min, the auxiliary blade speed is 250~320 r / min, and the mixing time is 10~15 min.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. New energy vehicles are designed with environmental protection in mind. The ceramic brake pads for new energy vehicles provided by this invention have zero heavy metal content. They use more environmentally friendly composite ceramic materials to replace the role of metals, which can prevent pollution to the environment during use. The ceramic brake pads provided by this invention can greatly reduce the noise generated by the vehicle braking system. Moreover, the brake pads have the characteristics of heat resistance, wear resistance, and resistance to wear and friction, which improves the strength of the friction material and limits deformation, thereby effectively improving the service life of the brake pads.
[0015] 2. This invention discloses a ceramic brake pad for new energy vehicles and its preparation method. The preparation method of the ceramic brake pad for new energy vehicles provided by this invention can effectively and quickly prepare the ceramic brake pad for new energy vehicles with high production efficiency. Attached Figure Description
[0016] Figure 1 This is a process flow diagram of the preparation method of the present invention; Figure 2 The results of NVH performance tests for three instances were obtained after performing the SAE J2521 test standard on the LINK3900 bench. Figure 3 Thermal degradation performance test results after performing extreme condition tests using the SAE J2522 high temperature and high load program on three instances; Figure 4 Brake pad wear performance test results after performing SAE J2522 high-load procedure extreme condition test on three instances; Figure 5 The results of SAE J2522 tests, including high-speed braking, cold braking, break-in cycle, and nominal coefficient of friction, were performed on three instances. Detailed Implementation
[0017] To enable those skilled in the art to better understand the present invention, the technical solution of the present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0018] In the description of this application, it should be noted that the directional terms such as "center", "lateral", "longitudinal", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", and "counterclockwise" indicate the orientation and positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. They should not be construed as limiting the specific protection scope of this application.
[0019] It should be noted that the terms "first," "second," etc., in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0020] Example 1
[0021] During the friction process, a smooth lubricating friction surface is formed on the brake pad surface. By adjusting the raw material composition and proportion, the resulting friction material has moderate hardness and high matching degree with the brake disc, thereby effectively reducing the noise generated during braking, improving the strength of the friction material and improving the friction and wear performance.
[0022] In this embodiment, the composite wear-resistant and noise-reducing material component accounts for 38% of the total weight of the raw materials, the composite heat-resistant and high-temperature resistant material component accounts for 37% of the total weight of the raw materials, and the composite friction material regulating component accounts for 25% of the total weight of the raw materials.
[0023] The composite wear-resistant and noise-reducing material group contains 6% by mass of potassium magnesium titanate flakes, 6% by mass of silicon carbide, 8% by mass of tin sulfide, 5% by mass of CIRCOLIT-T powder, 6% by mass of fiber filler, and 7% by mass of composite silicate whiskers. The composite heat-resistant and high-temperature resistant material group contains 4% aramid fiber, 7% silicon boron nitrogen carbon fiber, 8% hafnium carbide, 7% zirconium dioxide nanofiber, 4% polycrystalline mullite fiber, and 7% high-alumina aluminum silicate by mass percentage. The composite friction material adjustment group contains 5% by weight of special phenolic resin, 8% by weight of cashew shell oil friction powder, 6% by weight of quartz fiber, and 6% by weight of silicon nitride fiber.
[0024] Adding a composite heat-resistant and high-temperature resistant material group to the raw materials can quickly establish a porous and dense mesh structure in the brake pad friction material during vehicle braking. This allows the heat from the brake pad to be quickly transferred to the surrounding air through the mesh structure, thereby improving the thermal stability of the friction material, resisting thermal expansion and thermal cracking at high temperatures, and avoiding the risk of failure caused by thermal deformation and softening at high temperatures during braking. By mixing composite wear-resistant and noise-reducing material groups and composite heat-resistant and high-temperature resistant material groups in different proportions in the raw materials, the composite wear-resistant and noise-reducing material group will regularly fill the composite heat-resistant and high-temperature resistant material group, thereby establishing a three-dimensional porous and dense structure in the friction material layer, forming a composite friction material with excellent comprehensive performance.
[0025] In this embodiment, the composite wear-resistant and noise-reducing material group and the composite heat-resistant and high-temperature resistant material group have a ratio of approximately 1:1. This ratio can effectively reduce the noise and vibration generated during braking, improve the strength of the friction material and improve the friction and wear performance. It can also improve the thermal stability of the friction material, resist the thermal expansion and thermal cracking problems at high temperatures, and avoid the failure risk caused by thermal deformation and softening at high temperatures during braking. It has excellent overall performance.
[0026] Please see the appendix Figure 1 As shown, the above-mentioned method for preparing ceramic brake pads for new energy vehicles specifically includes the following steps: S1. Prepare raw materials: Potassium magnesium titanate flakes, silicon carbide, tin sulfide, CIRCOLIT-T powder, fiber filler, and composite silicate whiskers are placed in an automatic mixer in proportion to form a composite wear-resistant and noise-reducing material group. Aramid fiber, silicon boron nitrogen carbon fiber, hafnium carbide, zirconium dioxide nanofiber, polycrystalline mullite fiber, and high-alumina aluminum silicate are placed in an automatic mixer in proportion to form a composite heat-resistant and high-temperature resistant material group. Special phenolic resin, cashew shell oil friction powder, quartz fiber, and silicon nitride fiber are placed in an automatic mixer in proportion to form a composite friction material adjustment group. The prepared composite wear-resistant and noise-reducing material group, composite heat-resistant and high-temperature resistant material group, and composite friction material adjustment group are placed in an automatic mixer for orderly integration to obtain the raw materials. S2. Thermoforming: The raw material prepared in step S1 is placed in a semi-automatic single-cylinder single-cavity multi-station equal density rotary press for semi-finished product forming and pressing. The hot pressing pressure in this step is 30 MPa, the hot pressing temperature is 200℃, and the hot pressing time is 360 s. S3. Heat curing: Place the brake pad semi-finished product prepared in step S2 in an oven for heat curing. Step 1: Slowly raise the temperature from room temperature to 180℃ and cure for 1 hour. Step 2: Rapidly raise the temperature from 180℃ to 220℃ and cure for 1.5 hours. After curing, allow the temperature to drop naturally. Open the oven door when the temperature drops below 80℃. After the temperature drops to room temperature, take out the brake pad semi-finished product. S4. Final processing: Place the brake pad semi-finished product prepared in step S3 into an automatic grinding equipment to complete the processing of flat grinding, grooving, chamfering, and oblique grooves and J-shaped angles of the brake pad. S5. Ablation process: The brake pads that have completed the final processing in step S4 are placed in a brake pad ablation machine to automatically complete the ablation process. After the ablation machine is rapidly heated from room temperature to 550°C, the friction surface of the brake pads is attached to the ablation machine and ablated for 5 minutes before the brake pads are removed.
[0027] Specifically, in step S1, when preparing the composite wear-resistant and noise-reducing material group, the automatic mixing machine's blade speed is 2400 r / min, the secondary blade speed is 650 r / min, and the mixing time is 8 min; when preparing the composite heat-resistant and high-temperature resistant material group, the automatic mixing machine's blade speed is 1900 r / min, the secondary blade speed is 500 r / min, and the mixing time is 8 min; when preparing the composite friction material adjustment group, the automatic mixing machine's blade speed is 2300 r / min, the secondary blade speed is 750 r / min, and the mixing time is 6 min; when mixing the composite wear-resistant and noise-reducing material group, the composite heat-resistant and high-temperature resistant material group, and the composite friction material adjustment group, the automatic mixing machine's blade speed is 1500 r / min, the secondary blade speed is 280 r / min, and the mixing time is 10 min.
[0028] Example 2
[0029] The difference between this embodiment and Embodiment 1 is that: In this embodiment, the composite wear-resistant and noise-reducing material component accounts for 44% of the total weight of the friction material, the composite heat-resistant and high-temperature resistant material component accounts for 31% of the total weight of the friction material, and the composite friction material regulating component accounts for 25% of the total weight of the friction material. The ratio of the composite wear-resistant and noise-reducing material component to the composite heat-resistant and high-temperature resistant material component is approximately 4:3.
[0030] Specifically, the composite wear-resistant and noise-reducing material group contains 8% by mass of potassium magnesium titanate flakes, 7% by mass of silicon carbide, 10% by mass of tin sulfide, 8% by mass of CIRCOLIT-T powder, 9% by mass of fiber filler, and 8% by mass of composite silicate whiskers. The composite heat-resistant and high-temperature resistant material group contains 3% aramid fiber, 5% silicon boron nitrogen carbon fiber, 5% hafnium carbide, 4% zirconium dioxide nanofiber, 4% polycrystalline mullite fiber, and 4% high-alumina aluminum silicate by mass percentage. The composite friction material adjustment group contains 5% by weight of special phenolic resin, 8% by weight of cashew shell oil friction powder, 6% by weight of quartz fiber, and 6% by weight of silicon nitride fiber.
[0031] The difference in preparation method compared to Example 1 is as follows: S2. Thermoforming: The raw material prepared in step S1 is placed in a semi-automatic single-cylinder single-cavity multi-station equal density rotary press for semi-finished product forming and pressing. The hot pressing pressure in this step is 32 MPa, the hot pressing temperature is 230℃, and the hot pressing time is 340 s. S3. Heat curing: Place the brake pad semi-finished product prepared in step S2 in an oven for heat curing. Step 1: Slowly raise the temperature from room temperature to 170℃ and cure for 1 hour. Step 2: Rapidly raise the temperature from 170℃ to 210℃ and cure for 1.5 hours. After curing, allow the temperature to drop naturally. Open the oven door when the temperature drops below 80℃. After the temperature drops to room temperature, take out the brake pad semi-finished product. Specifically, in step S1, when preparing the composite wear-resistant and noise-reducing material group, the automatic mixing machine's blade speed is 2200 r / min, the secondary blade speed is 500 r / min, and the mixing time is 10 min; when preparing the composite heat-resistant and high-temperature resistant material group, the automatic mixing machine's blade speed is 2000 r / min, the secondary blade speed is 550 r / min, and the mixing time is 10 min; when preparing the composite friction material adjustment group, the automatic mixing machine's blade speed is 2500 r / min, the secondary blade speed is 800 r / min, and the mixing time is 8 min; when mixing the composite wear-resistant and noise-reducing material group, the composite heat-resistant and high-temperature resistant material group, and the composite friction material adjustment group, the automatic mixing machine's blade speed is 1600 r / min, the secondary blade speed is 260 r / min, and the mixing time is 12 min.
[0032] Example 3
[0033] The difference between this embodiment and Embodiment 1 is that: In this embodiment, the composite wear-resistant and noise-reducing material component accounts for 33% of the total weight of the friction material, the composite heat-resistant and high-temperature resistant material component accounts for 42% of the total weight of the friction material, and the composite friction material regulating component accounts for 25% of the total weight of the friction material. The ratio of the composite wear-resistant and noise-reducing material component to the composite heat-resistant and high-temperature resistant material component is approximately 3:4.
[0034] Specifically, the composite wear-resistant and noise-reducing material group contains 5% by mass of potassium magnesium titanate flakes, 4% by mass of silicon carbide, 6% by mass of tin sulfide, 7% by mass of CIRCOLIT-T powder, 6% by mass of fiber filler, and 5% by mass of composite silicate whiskers. The composite heat-resistant and high-temperature resistant material group contains 3% aramid fiber, 8% silicon boron nitrogen carbon fiber, 9% hafnium carbide, 8% zirconium dioxide nanofiber, 5% polycrystalline mullite fiber, and 6% high-alumina aluminum silicate by mass percentage. The composite friction material adjustment group contains 5% by weight of special phenolic resin, 8% by weight of cashew shell oil friction powder, 6% by weight of quartz fiber, and 6% by weight of silicon nitride fiber.
[0035] The difference in preparation method compared to Example 1 is as follows: S2. Thermoforming: The raw material prepared in step S1 is placed in a semi-automatic single-cylinder single-cavity multi-station equal density rotary press for semi-finished product forming and pressing. The hot pressing pressure in this step is 26 MPa, the hot pressing temperature is 180℃, and the hot pressing time is 300 s. S3. Heat curing: Place the brake pad semi-finished product prepared in step S2 in an oven for heat curing. Step 1: Slowly raise the temperature from room temperature to 200℃ and cure for 1 hour. Step 2: Rapidly raise the temperature from 200℃ to 250℃ and cure for 1.5 hours. After curing, allow the temperature to drop naturally. Open the oven door when the temperature drops below 80℃. After the temperature drops to room temperature, take out the brake pad semi-finished product. Specifically, in step S1, when preparing the composite wear-resistant and noise-reducing material group, the automatic mixing machine's blade speed is 2600 r / min, the secondary blade speed is 750 r / min, and the mixing time is 7 min; when preparing the composite heat-resistant and high-temperature resistant material group, the automatic mixing machine's blade speed is 2300 r / min, the secondary blade speed is 700 r / min, and the mixing time is 8 min; when preparing the composite friction material adjustment group, the automatic mixing machine's blade speed is 2200 r / min, the secondary blade speed is 850 r / min, and the mixing time is 5 min; when mixing the composite wear-resistant and noise-reducing material group, the composite heat-resistant and high-temperature resistant material group, and the composite friction material adjustment group, the automatic mixing machine's blade speed is 1700 r / min, the secondary blade speed is 320 r / min, and the mixing time is 15 min.
[0036] Please see the appendix Figures 2 to 5 The test comparison data records for each embodiment shown are used to draw conclusions from the test results: In Example 1, the composite wear-resistant and noise-reducing material group and the composite heat-resistant and high-temperature resistant material group have a ratio of approximately 1:1. This formulation effectively regulates the overall temperature resistance, wear resistance, and NVH performance of the materials. Test results show that the formulation has stable wear resistance, noise reduction, vibration reduction, heat resistance, and high-temperature resistant performance. The noise level above 70 dB in the 2KHz-16KHz range is less than 1%, achieving a noise level of AAA. Furthermore, the nominal coefficient of friction when matched with the brake disc reaches 0.46, and the brake pads show no thermal fade. After road testing, the brake pads showed minimal wear, and the disc surface remained intact without peeling after the road test. The lifespan can reach over 120,000 kilometers, making this the best example of the present invention.
[0037] In Example 2, the ratio of composite wear-resistant and noise-reducing material to composite heat-resistant and high-temperature resistant material is 4:3. The higher proportion of composite wear-resistant and noise-reducing material effectively reduces the noise generated during braking, improves the strength of friction materials and enhances friction and wear performance, resulting in significant noise reduction. Noise levels above 70 dB in the 2KHz-16KHz range are also less than 1%, with the noise level being AAA.
[0038] In Example 3, the ratio of composite wear-resistant and noise-reducing material to composite heat-resistant and high-temperature resistant material is 3:4. The higher proportion of composite heat-resistant and high-temperature resistant material effectively improves the thermal stability of the friction material, resists thermal expansion and thermal cracking at high temperatures, and has obvious heat-resistant and high-temperature resistant effects.
[0039] The above descriptions are merely embodiments of the present invention. Commonly known structures and characteristics of the solutions are not described in detail here. Those skilled in the art are aware of all common technical knowledge in the field prior to the application date or priority date, are aware of all existing technologies in that field, and have the ability to apply conventional experimental methods prior to that date. Those skilled in the art can, under the guidance of this application, improve and implement this solution in combination with their own capabilities. Some typical known structures or methods should not be obstacles for those skilled in the art to implement this application. It should be noted that those skilled in the art can make several modifications and improvements without departing from the structure of the present invention. These should also be considered within the scope of protection of the present invention, and will not affect the effectiveness of the implementation of the present invention or the practicality of the patent.
Claims
1. A ceramic brake pad for new energy vehicles, characterized in that, The raw materials, which are composed of a composite wear-resistant and noise-reducing material group, a composite heat-resistant and high-temperature resistant material group, and a composite friction material regulating group, are produced by thermoforming, thermosetting, and ablation. The composite wear-resistant and noise-reducing material group accounts for 25-59% of the total, the composite heat-resistant and high-temperature resistant material group accounts for 26-58% of the total, and the composite friction material regulating group accounts for 18-38% of the total. The total amount of the above components is 100%. The composite wear-resistant and noise-reducing material group contains 5-9% by weight of potassium magnesium titanate flakes, 3-8% by weight of silicon carbide, 3-10% by weight of tin sulfide, 4-10% by weight of CIRCOLIT-T powder, 5-12% by weight of fiber filler, and 5-10% by weight of composite silicate whiskers. The composite heat-resistant and high-temperature resistant material group contains aramid fiber with a mass percentage content of 2-6%, silicon boron nitrogen carbon fiber with a mass percentage content of 4-8%, hafnium carbide with a mass percentage content of 5-10%, zirconium dioxide nanofiber with a mass percentage content of 5-9%, polycrystalline mullite fiber with a mass percentage content of 5-13%, and high-alumina aluminum silicate with a mass percentage content of 5-12%. The composite friction material adjustment group contains 5-10% by weight of special phenolic resin, 6-12% by weight of cashew shell oil friction powder, 3-8% by weight of quartz fiber, and 4-8% by weight of silicon nitride fiber.
2. The method for preparing ceramic brake pads for new energy vehicles according to claim 1, characterized in that, Includes the following steps: S1. Prepare raw materials: Potassium magnesium titanate flakes, silicon carbide, tin sulfide, CIRCOLIT-T powder, fiber filler, and composite silicate whiskers are placed in an automatic mixer in proportion to form a composite wear-resistant and noise-reducing material group. Aramid fiber, silicon boron nitrogen carbon fiber, hafnium carbide, zirconium dioxide nanofiber, polycrystalline mullite fiber, and high-alumina aluminum silicate are placed in an automatic mixer in proportion to form a composite heat-resistant and high-temperature resistant material group. Special phenolic resin, cashew shell oil friction powder, quartz fiber, and silicon nitride fiber are placed in an automatic mixer in proportion to form a composite friction material adjustment group. The prepared composite wear-resistant and noise-reducing material group, composite heat-resistant and high-temperature resistant material group, and composite friction material adjustment group are placed in an automatic mixer for orderly integration to obtain the raw materials. S2. Thermoforming: The raw material prepared in step S1 is placed in a semi-automatic single-cylinder single-cavity multi-station equal density rotary press for semi-finished product forming and pressing. The hot pressing pressure in this step is 25-35 MPa, the hot pressing temperature is 180-220℃, and the hot pressing time is 300-420 s. S3. Heat curing: Place the brake pad semi-finished product prepared in step S2 in an oven for heat curing. Step 1: Slowly raise the temperature from room temperature to 150~200℃ and cure for 1 hour. Step 2: Rapidly raise the temperature from 150~200℃ to 200~260℃ and cure for 1.5 hours. After curing, allow the temperature to drop naturally. Open the oven door when the temperature drops below 80℃. Remove the brake pad semi-finished product after the temperature drops to room temperature. S4. Final processing: Place the brake pad semi-finished product prepared in step S3 into an automatic grinding equipment to complete the processing of flat grinding, grooving, chamfering, and oblique grooves and J-shaped angles of the brake pad. S5. Ablation process: The brake pads that have completed the final processing in step S4 are placed in a brake pad ablation machine to automatically complete the ablation process. After the ablation machine is rapidly heated from room temperature to 550°C, the friction surface of the brake pads is attached to the ablation machine and ablated for 5 minutes before the brake pads are removed.
3. The preparation method according to claim 2, characterized in that: In step S1, when preparing the composite wear-resistant and noise-reducing material group, the automatic mixer blade speed is 2000~2600 r / min, the auxiliary blade speed is 500~750 r / min, and the mixing time is 6~10 min.
4. The preparation method according to claim 3, characterized in that: In step S1, when preparing the composite heat-resistant and high-temperature resistant material group, the automatic mixer blade speed is 1800~2300 r / min, the auxiliary blade speed is 450~700 r / min, and the mixing time is 6~10 min.
5. The preparation method according to claim 4, characterized in that: In step S1, when preparing the composite friction material adjustment group, the automatic mixer blade speed is 2200~2800 r / min, the auxiliary blade speed is 700~850 r / min, and the mixing time is 5~8 min.
6. The preparation method according to claim 5, characterized in that: In step S1, when mixing the composite wear-resistant and noise-reducing material group, the composite heat-resistant and high-temperature resistant material group, and the composite friction material adjustment group, the automatic mixer blade speed is 1500~1700 r / min, the auxiliary blade speed is 250~320 r / min, and the mixing time is 10~15 min.
Citation Information
Patent Citations
Friction material
CN107620773A
High-performance copper-free environment-friendly ceramic friction material and manufacturing process thereof
CN108545997A
